NO solubility in water and brine up to 60 MPa and 373 K by combining Raman spectroscopy and molecular simulation. (25th January 2021) - Sterpenich, Jérôme; Caumon, Marie‐Camille; Lachet, Véronique; Creton, Benoit; El Jarmouni, Mohamed; Randi, Aurélien; Robert, Pascal
Abstract: In the processes of carbon capture and storage, sulfur and nitrogen oxides (SOx and NOx ) would be possibly injected with CO2 depending on the origin of CO2 . The thermodynamic properties of these gases in saline aquifer are poorly known. Solubility is one of the key parameter to be implemented in geochemical codes modelling long‐term evolution of the aquifer after injection. The solubility of NO is known only at atmospheric pressure. In this study, the solubility of NO in water and NaCl solutions was measured by Raman spectroscopy in the ranges 295–373 K and 2–60 MPa using a high pressure optical cell and after calibration on a few data from molecular simulations. The results show a decrease of solubility when temperature increases and when salinity increases. No modification of NO speciation was observed. Abstract : For the first time, the solubility of NO in water and NaCl solutions was measured by Raman spectroscopy in the ranges 295–373 K and 2–60 MPa using a high pressure optical cell and after calibration on a few data from molecular simulations. The results show a decrease of solubility when temperature increases and when salinity increases. No modification of NO speciation was observed.